Perceptual and acoustic parameters of vocal nodules in children - Joia Gramuglia, Andrea Cristina [UNESP]; Tavares, Elaine L. M. [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Martins, Regina Helena Garcia [UNESP] (Elsevier B.V., 2014)
Vocal nodules constitute the major cause of dysphonia during childhood. Auditory-perceptual and acoustic vocal analyses have been used to differentiate vocal nodules from normal voice in children.Purpose: To study the value of auditory-perceptual and acoustic vocal analyses in assessments of children with nodules.Design: Diagnostic test study.Patients and interventions: A comparative study was carried out including 100 children with videolaryngoscopic diagnosis of vocal nodules (nodule group-NG); and 100 children without vocal symptoms and with normal videolaryngoscopic exams (control group-CG). The age range of both groups was between 4 and 11 years. All children underwent auditory-perceptual vocal analyses (GRBASI scale); maximum phonation time and s/z ratio were calculated, and acoustic vocal analysis (MDVP software) were carried out.Results: There was no difference in the values of maximum phonation time and s/z ratio between groups. Auditory-perceptual analysis indicated greater compromising of voice parameters for NG, compared to CG: G (79 versus 24), R (53 versus 3), B (67 versus 23) and S (35 versus 1). The values of acoustic parameters jitter, PPQ shimmer, APQ, NHR and SPI were higher for NG for CG. The parameter f0 did not differ between groups.Conclusion: Compromising of auditory-perceptual (G, R, B and S) and acoustic vocal parameters (jitter, PPQ shimmer, APQ, NHR and SPI) was greater for children with nodules than for those of the control group, which makes them important methods for assessing child dysphonia. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Child; Dysphonia; Nodules; Hoarseness; Auditory-perceptual vocal analysis; Acoustic vocal analysis